2022
DOI: 10.1111/jifm.12166
|View full text |Cite
|
Sign up to set email alerts
|

Industries' heterogeneous reactions during the COVID‐19 outbreak: Evidence from Chinese stock markets

Abstract: This study examines the heterogeneous effects of the COVID‐19 outbreak on stock prices in China. We confirm what is already known, that the pandemic has had a significant negative impact on stock market returns. Additionally, we find, this effect is heterogeneous across industries. Second, fear sentiment can directly cause stock prices to fall and panic exacerbates the negative impact of the pandemic on stock returns. Third, and most importantly, we demonstrate the underlying mechanisms of four firm characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…However, the mere availability of accounting data at low frequencies, such as quarterly, limits the flexibility to examine the effect pattern of events in a timely manner (Tinoco and Wilson, 2013). On the contrary, stock prices have the advantage of quickly reflecting the systemic risks (Rees, 1990), including information about risk and cash flows that are not included in the financial statements (Hillegeist et al , 2004; Beaver et al , 2005; Agarwal and Taffler, 2008; Liu et al , 2022). Therefore, in this study, we focus on the reaction of bank stock prices to the war event.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mere availability of accounting data at low frequencies, such as quarterly, limits the flexibility to examine the effect pattern of events in a timely manner (Tinoco and Wilson, 2013). On the contrary, stock prices have the advantage of quickly reflecting the systemic risks (Rees, 1990), including information about risk and cash flows that are not included in the financial statements (Hillegeist et al , 2004; Beaver et al , 2005; Agarwal and Taffler, 2008; Liu et al , 2022). Therefore, in this study, we focus on the reaction of bank stock prices to the war event.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Baker et al (2020) show that no previous pandemics, like the Spanish flu and SARS, affected the financial markets as profoundly as COVID-19. The effect of the pandemic has been also documented in the Chinese stock market ( Liu et al, 2022 ). Assessing public perception as proxied by internet users, Costola et al (2020) and Smales (2021) provide evidence of the relationship between Google search volumes on the new coronavirus and financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…Banerjee (2022), , and Cicchiello et al (2022) put forth a similar revelation by examining different asset classes that, irrespective of the asset under consideration, each asset valuation got impacted to various degrees with riskiness increasing over time. Whilst studying the mixed impact of the pandemic on stock markets, Liu et al (2022) reported that the COVID-19 outbreak significantly adversely impacted the stock market, especially the labour-intensive industries. Akhtaruzzaman et al (2021b) examined the gold serving as a safe haven during the outbreak.…”
Section: Introductionmentioning
confidence: 99%